CONCEPTUAL METAPHORS IN ‘THE DEAD OF WINTER’ BY CHRIS PRIESTLEY - Peradze, Nato (Online Journal of Humanities ETAGTSU, 2024)
Children’s Gothic horror literature has been one of the developing directions in children’s literature nowadays. The research below concentrates on the Gothic chiller The Dead of Winter and its analysis within the cognitive metaphor theory (CMT) framework. The study aims to identify creative, conventional linguistic expressions and their corresponding conceptual metaphors. Selected linguistic expressions were grouped into different categories regarding their relevance; specifically, these are metaphors related to setting, natural phenomena, culture, characters, emotions and states. The findings of this study can be employed in different branches of humanities, including linguistic stylistics, cognitive linguistics, and theory of literature. Full Text (PDF)